2007
DOI: 10.2217/17435889.2.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E TPGS-Emulsified Poly(Lactic-Co-Glycolic Acid) Nanoparticles for Cardiovascular Restenosis Treatment

Abstract: The structure, physiology, and fate of living cells are all highly sensitive to mechanical forces in the cellular microenvironment, including stresses and strains that originate from encounters with the extracellular matrix (ECM), blood and other flowing materials, and neighbouring cells. This relationship between context and physiology bears tremendous implications for the design of cellular micro-or nanotechnologies, since any attempt to control cell behavior in a device must provide the appropriate physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 86 publications
1
23
0
Order By: Relevance
“…21 Some drugs, including therapeutic antisense, have been loaded into PLGA-NP to prevent or inhibit restenosis in experimental models. [28][29][30] In our preliminary study, we found that carbopol 940 was a good carrier, and the release curve of carbopol-encapsulated RAP-PLGA-NP ex vitro fits the Higuchi model. 23 The present study showed that local intravascular perfusion with RAP-PLGA-NP before grafting had good biocompatibility.…”
mentioning
confidence: 73%
“…21 Some drugs, including therapeutic antisense, have been loaded into PLGA-NP to prevent or inhibit restenosis in experimental models. [28][29][30] In our preliminary study, we found that carbopol 940 was a good carrier, and the release curve of carbopol-encapsulated RAP-PLGA-NP ex vitro fits the Higuchi model. 23 The present study showed that local intravascular perfusion with RAP-PLGA-NP before grafting had good biocompatibility.…”
mentioning
confidence: 73%
“…To evaluate cellular uptake of polymeric nanoparticles composed of poly-(lactic-co-glycolic acid) (PLGA) and coated with PVA and vitamin E TPGS, human colon adenocarcinoma cells were exposed in vitro [52]. It was found that vitamin E TPGS-coated PLGA NPs showed 1.4 folds higher cellular uptake than that of PVA-coated PLGA nanoparticles [53].…”
Section: Uptake Of Nanoparticles and Their Efects On Biological Membrmentioning
confidence: 99%
“…The major pharmacokinetic parameters (peak plasma concentration and total amount of drug delivered) for NK911-incorporated doxorubicin were approximately 36-fold and 29-fold (respectively) higher in plasma than free doxorubicin [47]. Other functional This is a post-print version of the following article: Gu, Zi, Rolfe, Barbara E., Thomas [48][49][50]. Another approach to surfacemodifying polymeric nanoparticles is utilization of positively-charged compounds.…”
Section: Nanoparticle Delivery Systemsmentioning
confidence: 99%